A cautionary note about messages of hope: Focusing on progress in reducing carbon emissions weakens mitigation motivation. (July 2016) - Hornsey, Matthew J.; Fielding, Kelly S.
Highlights: Emotional distress is strongly correlated with mitigation motivation; hope is not. Optimistic messages about carbon emissions reduce climate change risk perceptions. Less risk leads to less distress, which in turn lowers mitigation motivation. Pessimistic climate change messages avoid complacency without eroding efficacy. Abstract: For the first time this millennium, growth in carbon emissions has slowed. Indeed, the year 2014 was the first time in 40 years that the planet saw zero growth in emissions. We examine whether this message of progress can be effective in motivating people to engage in mitigation efforts. This question dovetails with commentary suggesting that gloomy messages about climate change risk fatiguing the population, and that alternative approaches are necessary. It is also informed by work suggesting that hope is a motivating force in terms of engaging in collective action and social change. Study 1 ( N  = 574) showed that negative emotions were strongly related to mitigation motivation and feelings of efficacy, but hope-related emotions had a much weaker relationship with these constructs. In the main experiment (Study 2: N  = 431) participants read an optimistic, pessimistic, or neutral message about the rate of progress in reducing global carbon emissions. Relative to the pessimistic message, the optimistic message reduced participants' sense that climate change represented a risk to them, and the associated feelings of distress. Consequently, the optimistic message was less successful in increasing mitigation motivation than the pessimistic message. In sum, predictions that the optimistic message would increase efficacy did not transpire; concerns that the optimistic message would increase complacency did transpire. Recent progress in curbing global carbon emissions is welcome, but we found no evidence that messages focusing on this progress constitute an effective communication strategy.